2002
DOI: 10.1111/1467-6494.00180
|View full text |Cite
|
Sign up to set email alerts
|

Defense Mechanisms, Behavior, and Affect in Young Adulthood

Abstract: The relationship between defense mechanism use, observed behavior, and affect was investigated in a sample of 91 young adults. Defense mechanisms were assessed using Cramer's (1991a) Defense Mechanism Manual for TAT stories; behavior was based on observer Q-sort ratings (Block, 1978). The findings show that men and women who rely on the immature defense of denial at age 23 show multiple signs of behavioral immaturity, as well as anxiety. In contrast, extensive use of projection was related to a suspicious, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…Concordance of target and best‐friend reports. Gender differences in the correlations were not postulated but were nevertheless explored, given that past research on perfectionism and maladjustment has seldom distinguished the results for males versus females, and past evidence suggest that the correlates of defense style may differ for males and females (Cramer, 2002). Preliminary correlation analyses revealed only one clear gender difference — analyses of peer ratings showed that other‐oriented perfectionism in female targets was not linked with defense style measures, but other‐oriented perfectionism in male targets was associated with neurotic and immature defenses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordance of target and best‐friend reports. Gender differences in the correlations were not postulated but were nevertheless explored, given that past research on perfectionism and maladjustment has seldom distinguished the results for males versus females, and past evidence suggest that the correlates of defense style may differ for males and females (Cramer, 2002). Preliminary correlation analyses revealed only one clear gender difference — analyses of peer ratings showed that other‐oriented perfectionism in female targets was not linked with defense style measures, but other‐oriented perfectionism in male targets was associated with neurotic and immature defenses.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for at least some socially prescribed perfectionists, their personality style may reflect a hostile, paranoid tendency to project blame onto others. Paranoia and projection are generally believed to reflect immature defense styles (see Cramer, 2002; Vaillant, 1994).…”
Section: Perfectionism Coping and Defense Stylesmentioning
confidence: 99%
“…One possible explanation is that gender differences in the use of externalizing and internalizing defense mechanisms might be related to social mechanisms, as the stereotypical socialization pattern of the females includes an inhibition of overt hostility and aggression, while those kinds of behavior are tolerated, and even encouraged, in men (Cramer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the use of mature defenses is found to be associated with positive personality characteristics, such as empathy, higher self‐esteem, an internal locus of control, competence, self‐confidence, outgoingness, and a secure attachment style. In contrast, the use of immature defenses is associated with indications of difficulty, such as irresponsibility, self‐centeredness, unclear ‘fuzzy’ thinking, and anxiety (e.g., Cramer, 2002a,b; Cramer & Tracy, 2005; Davidson, McGregor, Johnson, Woody, & Chaplin, 2004; Hibbard et al., 2000; Romans, Martin, Morris, & Herbison, 1999; Whitty, 2003). Furthermore, use of mature defenses by young adults has predicted multiple indications of later positive adjustment, whereas immature defense use was related to later problems (Vaillant, 1993).…”
Section: Pillar III Defenses Are Part Of Normal Everyday Functioninmentioning
confidence: 99%